DEONTOLOGI VS. KONSEKUENSIALISME : PANDANGAN FILOSOFIS DALAM PENEGAKAN HUKUM HAK ASASI MANUSIA - Setiya Widayaka; Hananto Widodo; Tamsil; Fradhana Putra Disantara (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Enforcement of Human Rights (HAM) law is an effort to ensure that the basic rights of every individual can be respected, protected, safeguarded and fulfilled by the state and society. The deontological and consequentialist approaches have provided different views on upholding human rights. Deontology emphasizes moral obligations, namely that every action must be based on correct principles without prioritizing the consequences. This approach is sometimes less flexible in dealing with complex circumstances or cases and requires contextual adjustments. Meanwhile, consequentialism emphasizes the results and impacts of an action, where an action can be judged as good or bad based on the consequences of the action on the welfare of society, but risks sacrificing basic human rights principles for the sake of short-term results. This research aims to provide an analysis regarding how these two approaches are applied and the resulting impact on enforcing human rights law. That of these two approaches, neither approach is completely superior in enforcing human rights law. Both approaches have their respective advantages and disadvantages. Therefore, an approach that combines deontological principles with considerations of consequentialism is necessary to ensure and improve the just and prosperous enforcement of human rights law. Enforcement of human rights law ensures that the principles of justice, freedom and human dignity are upheld or respected in all aspects of life. The research method used in this research is normative research, namely a legal research method that focuses on analyzing legal norms and principles that develop in society.